Development and psychometric properties of the Patient-Head Injury Participation Scale (P-HIPS) and the Patient-Head Injury Neurobehavioral Assessment Scale (P-HINAS): patient and family determined outcomes scales - Deb, Shoumitro (Dove Medical Press, 2007)
OBJECTIVE: To develop a measure to assess post-acute outcome following from traumatic brain injury (TBI) with particular emphasis on the emotional and the behavioral outcome. The second objective was to assess the test–retest reliability, internal consistency, and factor structure of the newly developed patient version of the Head Injury Participation Scale (P-HIPS) and Patient-Head Injury Neurobehavioral Scale (P-HINAS). METHOD: Thirty-two TBI individuals and 27 carers took part in in-depth qualitative interviews exploring the consequences of the TBI. Interview transcripts were analyzed and key themes and concepts were used to construct the 49-item P-HIPS. A postal survey was then conducted on a cohort of 113 TBI patients to ‘field test’ the P-HIPS and the P-HINAS. RESULTS: All individual 49 items of the P-HIPS and their total score showed good test–retest reliability (0.93) and internal consistency (0.95). The P-HIPS showed a very good correlations with the Mayo Portland Adaptability Inventory-3 (MPAI-3) (0.87) and a moderate negative correlation with the Glasgow Outcome Scale-Extended (GOSE) (−0.51). Factor analysis extracted the following domains: ‘Emotion/Behavior,’ ‘Independence/Community Living,’ ‘Cognition’ and ‘Physical’. The ‘Emotion/Behavior’ factor constituted the P-HINAS, which showed good internal consistency (0.93), test–retest reliability (0.91) and concurrent validity with MPAI subscale (0.82). CONCLUSIONS: Both the P-HIPS and the P-HINAS show strong psychometric properties. The qualitative methodology employed in the construction stage of the questionnaires provided good evidence of face and content validity.